Dual Friction Mode Textile‐Based Tire Cord Triboelectric Nanogenerator. (12th August 2020) - Seung, Wanchul; Yoon, Hong‐Joon; Kim, Tae Yun; Kang, Minki; Kim, Jihye; Kim, Han; Kim, Seong Min; Kim, Sang‐Woo
Abstract: As vehicles become smarter, an alternative power solution will become increasingly important for future vehicle development. With this context, a triboelectric nanogenerator (TENG) is proposed which fully sits on tires and consists of textile‐based tire materials. Both polydimethylsiloxane‐coated silver textile, serving as an external tire tread material, and nylon woven textile, serving as an internal tire cord material, performing as opposing triboelectric materials, are well adaptable for rolling tires. It is demonstrated that tire material‐based TENG performs at its maximum as it makes mutual contact with the road. The power generation property is characterized under different driving situations such as different tire rotation speeds and varying numbers of devices on the tires. The TENG demonstrates a maximum output voltage and a current of about 225 V and 42 µA, respectively, along with an output power of 0.5 mW at optimum load. The work offers the possibility to not only directly operate minute power‐consuming electronics but also collect power and store it while driving a vehicle. Abstract : A textile‐based tire cord triboelectric nanogenerator (TC‐TENG) adaptable to tires exhibits power generation in the dual friction mode. Serving as tire parts, both tire tread and cord achieve contact with the road as well as mutually, leading to power generation via triboelectricity. TC‐TENG achieves ≈0.5 mW, presenting a strategy for harvesting mechanical energy while driving vehicles with minimum load and space inside tires.